The effect of intermittent fasting on hedonic hunger: a pilot prospective cohort study based on Ramadan intermittent fasting - Selen, Halime (Frontiers in Nutrition, 2025)
ObjectiveThis study aims to evaluate the changes in hedonic hunger (HH) during Ramadan intermittent fasting (RIF) and to investigate the role of HH as a factor influencing adherence to intermittent fasting (IF) regimens.MethodsThis prospective cohort study was conducted between February 24 and March 29, 2025, with 122 participants aged between 20 and 25. The study data were collected through face-to-face interviews using a questionnaire that included sociodemographic information and the power of food scale (PFS), administered 1 week before the beginning of Ramadan, and during the first, middle period and final weeks of the month. The PFS comprises three subscales: food available, food present, and food tasted. In general, mean scores of the PFS and its subdimensions exceeding 2.5 are interpreted as indicating a high tendency toward HH.ResultsDuring the first week of Ramadan, participants’ scores for food available (p = 0.016), food tasted (p = 0.002), and the PFS mean score (p = 0.048) were found to be significantly higher compared to the pre-Ramadan scores. However, no statistically significant differences were observed in the PFS mean and subscale scores between the pre-Ramadan period and the final week of RIF. Compared to the pre-Ramadan period, participants exhibited a mean reduction of 0.6 ± 1.51 kg in body weight (p < 0.001) and 0.3 ± 1.20 kg/m2 in BMI (p = 0.003) following RIF. A statistically significant but weak negative correlation was observed between changes in participants’ body weight and the scores of food available (r = −0.203, p = 0.025), food present (r = −0.340, p = p < 0.001), food tasted (r = −0.319, p < 0.001), and the PFS mean score (r = −0.323, p = p < 0.001). A statistically significant and weak negative correlation was found between changes in BMI and the scores of food present (r = −0.181, p = 0.046), food tasted (r = −0.216, p = 0.017), and the PFS mean score (r = −0.208, p = 0.021).ConclusionThis study suggests that higher levels of HH may be experienced at the onset of RIF practices; however, over time, individuals appear to adapt, returning to their pre-fasting levels of HH. Within the limited observation period of this study, the influence of RIF–a form of IF–on HH appears to be transient, suggesting that longer-term studies with larger sample sizes are needed to clarify its persistence.